Prevalence, Severity (ISTAP Classification), and Risk Factors of Skin Tears in Long-Term Care Residents: A Multi-Facility Cross-Sectional Study - Anna Lindström; Eriksson Johan; Karin Svensson; Michael O’Neill; Asmat Burhan (Journal of Wound Research and Technology, 2025)
Background: Skin tears remain a substantial, preventable harm in long-term geriatric care, yet exposure-aware benchmarks are scarce. Evidence quantifying how medical adhesive type and resident frailty relate to point prevalence and ISTAP severity in routine care is limited, hindering targeted prevention and procurement policies. Purposes: This study aimed to estimate skin-tear prevalence and severity, and to test associations of adhesive type and resident factors with these outcomes among older inpatients. Methods: In a cross-sectional study at Skånes universitetssjukhus, Malmö, Sweden (4 September–30 November 2024), we enrolled 243 adults aged >65 years meeting prespecified eligibility. Skin tears and ISTAP Types 1–3 were assessed by trained staff; adhesive exposure (acrylic vs silicone) and covariates (age, sex, CFS frailty, dermatoporosis, xerosis, comorbidities, cognition, prior tears, environment) were recorded. The primary outcomes were point prevalence and ordinal severity. We applied modified Poisson models for prevalence ratios and ordinal logistic regression for severity, adjusting for prespecified covariates, reporting effect estimates with 95% CIs. Sensitivity, subgroup, and interaction analyses were prespecified. Results: Among 243 residents (mean age 79.8; 58% women), point prevalence was 18.1%. Acrylic (vs silicone) adhesive was associated with higher prevalence (aPR 1.52, 95% CI 1.06–2.18) and greater ISTAP severity; frailty (per CFS point aPR 1.18, 95% CI 1.01–1.38), dermatoporosis (aPR 1.35, 95% CI 1.03–1.77), xerosis (aPR 1.44, 95% CI 1.03–2.03), and prior tears (aPR 1.62, 95% CI 1.09–2.41) were independent correlates. The acrylic effect was stronger at CFS ≥5 (interaction p=0.031). Findings were robust across sensitivity analyses. Conclusion: Selecting soft silicone adhesives and prioritising barrier care for frail, dermatoporotic residents may reduce skin-tear burden. Results support practice and procurement policies in geriatric/LTC wards and motivate multicentre longitudinal or pragmatic cluster-RCTs to assess durability and cost-effectiveness.